Manajemen Pemasaran Pendidikan Dalam Penerimaan Mahasiswa Baru Di STAI Jamiatut Tarbiyah Lhoksukon - Wahyuni, Suci (Yayasan Madinah Al-Aziziyah, 2023)
This study aims to find out how marketing management is applied by STAI Jamiatut Tarbiyah Lhoksukon to attract public interest to join in improving the quality of human resources (SDM). This research is a field study with a descriptive qualitative approach. The data source consists of primary and secondary data. Data collection techniques use observation, interviews and documentation. Data analysis is carried out by means of data reduction, data presentation and drawing conclusions on the data that has been collected. Meanwhile, to ensure the validity of the data, triangulation techniques are used with theory. The results of this study show that the STAI Jamiatut Tarbiyah Lhoksukon campus in conducting educational marketing uses several strategies, including: (1) Educational Marketing Planning is carried out by forming a selection committee for new student admissions and holding an annual meeting to discuss funds for the selection and procurement of promotions. (2) The implementation of Educational Marketing, among others: marketing through Blocks or the Web, marketing by sharing word of mouth / WOM (Word Of Mouth) , holdingworkshops or seminars related to information about STAI Jamiatut Tarbiyah Lhoksukon, installing billboards, browsing distribution, socializing to junior high schools / MTsN. (3) Supervision of educational marketing in order to find out the extent of performance and quota adjustment the incoming.